1998
DOI: 10.1083/jcb.141.6.1433
|View full text |Cite
|
Sign up to set email alerts
|

Differential Nuclear Translocation and Transactivation Potential of β-Catenin and Plakoglobin

Abstract: β-Catenin and plakoglobin are homologous proteins that function in cell adhesion by linking cadherins to the cytoskeleton and in signaling by transactivation together with lymphoid-enhancing binding/T cell (LEF/TCF) transcription factors. Here we compared the nuclear translocation and transactivation abilities of β-catenin and plakoglobin in mammalian cells. Overexpression of each of the two proteins in MDCK cells resulted in nuclear translocation and formation of nuclear aggregates. The β-catenin-containing n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
279
4
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 258 publications
(308 citation statements)
references
References 87 publications
24
279
4
1
Order By: Relevance
“…Numerous studies have implicated cell ± cell adhesion as a key regulatory point in the transition from benign to highly invasive tumors. Focus has been directed toward the tumor suppressor role of adhesion molecules such as cadherins, C-CAM, acatenin, and plakoglobin in tumor progression (BenZe'ev, 1997;Davies et al, 1998;Ewing et al, 1995;Simcha et al, 1996). Conn et al (1990) demonstrated that the loss of expression of major components of the desmosome correlated with invasiveness of TCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have implicated cell ± cell adhesion as a key regulatory point in the transition from benign to highly invasive tumors. Focus has been directed toward the tumor suppressor role of adhesion molecules such as cadherins, C-CAM, acatenin, and plakoglobin in tumor progression (BenZe'ev, 1997;Davies et al, 1998;Ewing et al, 1995;Simcha et al, 1996). Conn et al (1990) demonstrated that the loss of expression of major components of the desmosome correlated with invasiveness of TCC.…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulation of adhesion-related molecules in tumors have indicated that these proteins may function as TSs (Birchmeier, 1995;Bullions et al, 1997;Hoover et al, 1998;Hsieh et al, 1995;Simcha et al, 1996;Taverna et al, 1998). The loss of E-cadherinmediated cell adhesion was shown to be an important rate-limiting step in the progression of several somatic and hereditary carcinomas (Berx et al, 1998;Birchmeier et al, 1996;Guilford et al, 1998;Hirohashi, 1998;Perl et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its associations with classic cadherins, plakoglobin interacts with desmosomal cadherins and is essential for the formation of desmosomes (Parker et al, 1998;Holthofer et al, 2007;Garrod and Chidgey, 2008), whereas b-catenin typically does not. Furthermore, although both b-catenin and plakoglobin can interact with the Tcf/Lef family of transcription factors, only the b-catenin-Tcf complexes have transcriptional activity, whereas the plakoglobin-Tcf complex is unable to bind DNA (Simcha et al, 1998;Zhurinsky et al, 2000a).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this structural role in cell adhesion, bcatenin and its Drosophila homolog, armadillo, are key components of the wg/wnt-signaling pathway (Peifer and Wieschaus, 1990;Peifer et al, 1993;Wodarz and Nusse, 1998) that regulates developmental processes, including speci®cation of the anterior-posterior segment polarity in Drosophila (Peifer et al, 1993), and axis determination in developing Xenopus embryos (Heasman et al, 1994). Signaling by b-catenin is carried out mainly by the nuclear pool of the protein, and recruitment of this protein to adherens junctions, by overexpressing cadherins inhibits its signaling activity (Fagotto et al, 1996;Sanson et al, 1996;Simcha et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the level of plakoglobin is often reduced in cancer cells (Navarro et al, 1993;Aberle et al, 1995;Simcha et al, 1996) and the human plakoglobin gene displays loss of heterozygosity in certain tumors (Aberle et al, 1995). Moreover, plakoglobin was shown to suppress tumorigenicity when overexpressed in various transformed cell lines (Simcha et al, 1996).…”
Section: Introductionmentioning
confidence: 99%